Analysis of the use of MT among professional translators and translator trainees of the School of English Language at UCSG. - Castro Egas, Susana María (2018)
This project explains the concept of Machine Translation and contrasts it with similar concepts. It provides details regarding the different types of machine translation, their origins and development through time and real-life use among translators as part of their translation processes. Different types of editing are presented, processes are defined and matched with the correspondent type of translation process. Further research was conducted to determine the most popular machine translation software among translation professionals and students, the frequency of use, the fields in which the use of MT is more commonplace, the purpose of using it, and the benefits of working with the software compared to full human translation processes. This study also provides a comparative evaluation of a product rendered through machine translation analyzing the quality of such product. It identifies the type of errors that most frequently occur as well as the ratings of each sentence rendered. This allowed to point out the aspects that need a strong focus in the post-editing process so that the final product is enhanced and validated.